Penggunaan Model Pembelajaran Student Teams Achievement Division (STAD) untuk Meningkatkan Motivasi dan Prestasi Belajar Matematika Siswa Kelas X - Juaini, Muhammad; Nofisulastri, Nofisulastri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
This study aims to: 1) Increase the motivation and achievement of students in class X IPS-2 SMA Negeri 3 Selong through the cooperative learning model of the Student Teams Achievement Division (STAD) type, 2) Describe the increase in motivation and achievement in learning mathematics in class X IPS -2 SMA Negeri 3 Selong through a cooperative learning model of the Student Teams Achievement Division (STAD) type. The solution to learning that is still teacher-centered and students' motivation in learning mathematics is still low is the cooperative learning model of the Student Teams Achievement Division (STAD) type. This research was conducted in two cycles of 34 students. Data collection techniques through observation, motivational questionnaires (ARCS Model) and written tests. Data analysis was performed using percentage techniques. The implementation of the cooperative learning model type Student Teams Achievement Division (STAD) is expressed in very good, good, good enough, not good, and not good categories, while the motivation to learn mathematics is expressed in very high, high, medium, low and very low categories. Based on the results of the research conducted, it can be concluded that 1) the implementation of the cooperative learning model of the Student Teams Achievement Division (STAD) type in cycle I was in the fairly good category and in the good category in cycle II; 2) The average motivation to learn mathematics in class X IPS-2 SMA Negeri 3 Selong in cycle I was 66% (low category), while in cycle II it increased to 71% (medium category).